2020
DOI: 10.3390/biom10091311
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Molecular Background of Endometrial Receptivity in Adenomyosis

Abstract: Background: Adenomyosis is a gynaecological condition with limited evidence of negative impact to endometrial receptivity. It is commonly associated with endometriosis, which has been shown to alter endometrial expression patterns. Therefore, the candidate genes identified in endometriosis could serve as a source to study endometrial function in adenomyosis. Methods: Transcripts/proteins associated with endometrial receptivity in women with adenomyosis or endometriosis and healthy women were obtained from publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 66 publications
0
15
0
1
Order By: Relevance
“…The ceRNA networks included 122 miRNAs and 137 mRNAs, which were closely related to nine signaling pathways. Some of them, such as Rap1 pathway ( 30 ) and leukocyte transendothelial migration pathway(including Intercellular Adhesion Molecule 1[ICAM-1) and Integrin Subunit Alpha L (ITGAL)] ( 31 , 32 ), have been proven as involved in endometriosis. The data suggest that these pathways might play a role in the pathogenesis and development of endometriosis via interacting with circRNAs.…”
Section: Circrnas In Endometriosismentioning
confidence: 99%
“…The ceRNA networks included 122 miRNAs and 137 mRNAs, which were closely related to nine signaling pathways. Some of them, such as Rap1 pathway ( 30 ) and leukocyte transendothelial migration pathway(including Intercellular Adhesion Molecule 1[ICAM-1) and Integrin Subunit Alpha L (ITGAL)] ( 31 , 32 ), have been proven as involved in endometriosis. The data suggest that these pathways might play a role in the pathogenesis and development of endometriosis via interacting with circRNAs.…”
Section: Circrnas In Endometriosismentioning
confidence: 99%
“…In our previous study [ 18 ], we gathered proteins, genes and functional noncoding RNAs (ncRNAs) shown to be dysregulated in the endometrium of women with adenomyosis during the expected window of implantation (WOI). Bioinformatics approaches were used to integrate retrieved loci with endometrial receptivity genes from the literature associated with healthy (normal) uteri to identify candidate dysregulated mechanisms involved in the regulation of embryo implantation in adenomyosis.…”
Section: Introductionmentioning
confidence: 99%
“…Bioinformatics approaches were used to integrate retrieved loci with endometrial receptivity genes from the literature associated with healthy (normal) uteri to identify candidate dysregulated mechanisms involved in the regulation of embryo implantation in adenomyosis. In addition, we included better characterized endometriosis as a model disorder to study the impact of gynaecological pathology on endometrial molecular organization [ 18 ]. Numerous published genome-wide studies associated with the endometrial molecular background in women with endometriosis enabled us to develop a catalogue of genes sorted according to the phases of the menstrual cycle [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations